Pro silverlight 3 in VB - MacDonald, Matthew.
Silverlight is a lightweight browser plug-in that frees your code from the traditional confines of the browser. It's a rules-changing, groundbreaking technology that allows you to run rich client applications right inside the browser. Even more impressively, it's able to host true .NET applications in non-Microsoft browsers (like Firefox) and on non-Microsoft platforms (like Mac OS X). Silverlight is still new and evolving fast, and you need a reliable guidebook to make sense of it. Pro Silverlight 3 in VB, Second Edition is the perfect reference to ensure you are informed and up to date: you'll learn about the features that put Silverlight in direct competition with Adobe Flash, such as rich support for 2D drawing, animations, and media playback, and best of all, you'll experience the plumbing of .NET and the design model of WPF through Silverlight—all of the same .NET technology that developers use to design next-generation Windows applications. Author Matthew MacDonald provides an expertly crafted tutorial written from professional developer to professional developer. You'll learn to create rich media applications using Silverlight in the environment you're most productive in—no matter what the target platform. Introducing Silverlight -- XAML -- Layout -- Dependency Properties and Routed Events -- Elements -- The Application Model -- Navigation -- Shapes and Geometries -- Brushes, Transforms, and Bitmaps -- Animation -- Sound, Video, and Deep Zoom -- Styles and Behaviors -- Templates and Custom Controls -- Browser Integration -- ASP.NET Web Services -- Data Binding -- Data Controls -- Isolated Storage -- Multithreading -- Networking.